2021
DOI: 10.1111/1756-185x.14167
|View full text |Cite
|
Sign up to set email alerts
|

Familial aggregation of juvenile idiopathic arthritis with other autoimmune diseases: Impact on clinical characteristics, disease activity status and disease damage

Abstract: Objectives To evaluate the impact of family history of autoimmune diseases (FHADs) on the clinical characteristics and outcome of juvenile idiopathic arthritis (JIA). Methods We retrospectively reviewed children with JIA seen in 7 pediatric rheumatology clinics from 6 Arab countries. All included patients met the International League of Associations for Rheumatology classification criteria for JIA and had a disease duration greater than 1 year. Data were collected at the last follow‐up visit and comprised clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…A small study by Tronconi et al [8] did not find an association between a family history of AD and the subtype and age at onset of JIA. On the contrary, the current study observed that patients with psoriatic arthritis, undifferentiated arthritis and ERA reported relatively often a family history of AD as opposed to patients with systemic arthritis and oligoarthritis, which is also in line with two previous studies [4,6]. The association between HLA-B27 and a family history of AD corresponds with the observed effect for JIA category, given that, 73.7% of ERA patients and 38.3% of undifferentiated arthritis patients in our study were HLA-B27 positive.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…A small study by Tronconi et al [8] did not find an association between a family history of AD and the subtype and age at onset of JIA. On the contrary, the current study observed that patients with psoriatic arthritis, undifferentiated arthritis and ERA reported relatively often a family history of AD as opposed to patients with systemic arthritis and oligoarthritis, which is also in line with two previous studies [4,6]. The association between HLA-B27 and a family history of AD corresponds with the observed effect for JIA category, given that, 73.7% of ERA patients and 38.3% of undifferentiated arthritis patients in our study were HLA-B27 positive.…”
Section: Discussionsupporting
confidence: 93%
“…This can be explained by the autoinflammatory instead of autoimmune nature of this JIA category [1]. Previous studies have reported contradictory relationships between the age at JIA onset and a family history of AD [5,6,8,[39][40][41]. In this study, familial AD was associated with older age at JIA onset.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations